Metalloproteinases are involved in the regulation of prenatal tooth morphogenesis - Janečková, Eva; Juarez-Balarezo, Jesus; Tucker, Abigail S; Matalová, Eva; Holomková, Kateřina; Gaete, Marcia (American journal of physiology. Cell physiology, 2025)
During development, tooth germs undergo various morphological changes resulting from interactions between the oral epithelium and ectomesenchyme. These processes are influenced by the extracellular matrix, the composition of which, along with cell adhesion and signaling, is regulated by metalloproteinases. Notably, these include matrix metalloproteinases (MMPs), a disintegrin and metalloproteinases (ADAMs), and a disintegrin and metalloproteinases with thrombospondin motifs (ADAMTSs). Our analysis of previously published scRNAseq datasets highlight that these metalloproteinases show dynamic expression patterns during tooth development, with expression in a wide range of cell types, suggesting multiple roles in tooth morphogenesis. To investigate this, Marimastat, a broad-spectrum inhibitor of MMPs, ADAMs, and ADAMTSs, was applied to ex vivo cultures of mouse molar tooth germs. The treated samples exhibited significant changes in tooth germ size and morphology, including an overall reduction in size and an inversion of the typical bell shape. The cervical loop failed to extend, and the central area of the inner enamel epithelium protruded. Marimastat treatment also disrupted proliferation, cell polarization, and organization compared with control tooth germs. In addition, a decrease in laminin expression was observed, leading to a disruption in continuity of the basement membrane at the epithelial-mesenchymal junction. Elevated hypoxia-inducible factor 1-alpha gene (Hif-1α) expression correlated with a disruption to blood vessel development around the tooth germs. These results reveal the crucial role of metalloproteinases in tooth growth, shape, cervical loop elongation, and the regulation of blood vessel formation during prenatal tooth development.NEW & NOTEWORTHY Inhibition of metalloproteinases during tooth development had a wide-ranging impact on molar growth affecting proliferation, cell migration, and vascularization, highlighting the diverse role of these proteins in controlling development.
Keywords: kyseliny hydroxamové; Hypoxia-Inducible Factor 1, alpha Subunit; faktor 1 indukovatelný hypoxií - podjednotka alfa; morfogeneze; Cell Proliferation; Mice, Inbred C57BL; Odontogenesis; Animals; blood vessels; Mice; Hydroxamic Acids; myši inbrední C57BL; Gene Expression Regulation, Developmental; vývojová regulace genové exprese; Morphogenesis; tooth germ morphogenesis; proliferace buněk; Tooth Germ; inhibitory matrixových metaloproteinas; metaloproteasy; metalloproteinases; zubní zárodek; zvířata; Matrix Metalloproteinase Inhibitors; odontogeneze; moláry; Metalloproteases; cervical loop; Molar; extracellular matrix; myši